THE USE OF AUTHENTIC MATERIAL IN TEACHING READING DESCRIPTIVE TEXT: REVIEW OF LITERATURE - Fitri Puspita Sari; Gusti Nur Hafifah; Linda Mayasari (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2020)
Process of learning needs development time by time. Following situation of teaching, it is important for educator to find materials which is understandable and enjoyable. One of materials that effective to be used is authentic material. The authentic materials are not designed for language learning, it is able to use as a tool to teach students and give them real experience in the classroom. Moreover, this paper aims to review research about authentic materials that is used in teaching and learning reading, especially (descriptive text). In order to get the goal, this paper reviews some researches from experts relating to the use of authentic materials in learning to read descriptive text. The author used around 40 articles which discussed about teaching English skills especially reading, authentic material and descriptive text. The author collected the data by surfing the international and national journal to be reviewed. The result shows that most of the studies recommend the educators use authentic materials to be applied in the classroom.